Converting polyolefin plastics into few-walled carbon nanotubes via a tandem catalytic process: importance of gas composition and system configuration - Veksha, Andrei (2022)
Polyolefins such as polyethylene (PE) and polypropylene (PP) are abundant components of plastic waste. Chemical recycling of PE and PP via pyrolysis followed by chemical vapor deposition typically results in the growth of multi-walled carbon nanotubes (CNTs). Here, a tandem catalytic system for the growth of few-walled CNTs is reported. The successful synthesis of few-walled CNTs in the system relies on the catalytic processing of pyrolysis gas from plastics into intermediate gas mixtures containing mainly paraffins and hydrogen (700 °C, catalyst: 40 wt% Co, 10 wt% Mo and 50 wt% MgO). Under appropriate conditions (1000 °C, catalyst: Co 3 wt%, Mo 2 wt% and MgO 95 wt%, synthesis time: 20 min), the obtained intermediate gas mixture was selectively converted into few-walled CNTs with > 95% CNTs having small outer diameters of 1-7 nm, containing CNTs with as little as three walls and having distinct radial breathing mode in Raman spectra at wave lengths 100-400 cm-1. The proposed synthesis process opens new opportunities for production of high value few-walled CNTs from plastic waste.